أثر المنهج التكاملي في تحصيل مهارات الكتابة العربية لدى طلبة المستوى الأول في المعهد العالي لأعداد المعلمين (النعيمي) بجاكرتا - Ali Abdullah Muthanna Al-Shaeri
The purpose of this research was to investigate the problem of insufficient scores in Arabic writing skills for students of Arabic as a second language at Mahad Aly (An-Nuaimy) Jakarta- Higher institute of teachers training.In the researchers opinion that, the complimentary approach can influence Arabic writing skills.Hence this experimental study was conducted in order to observe the effect of complimentary approach on teaching Arabic writing skills for the studentsof the first level at Jakarta Higher Institute of teachers training.A null hypothesis was formulated that there is no siqnihceut difference statistically significant at the level of 50.0 between the mean scores of the experimental group and the control group in the students Arabic writing achievements on the post-test measures as a result of using the complimentary approach. The “ Solomon Four Group Design “ of experiment was used.The experimental materials which were designed based on complimentary approach were applied to the experimental group.While the tradisional non complimentary approach was applied to the control group.Using the statistical Package for Social Sciences (SPSS) different measures were applied to analyze the data including averages, standard deviations degrees of freedom and t-tests.Finally the experimental procedures yielded the rejection of the null hypothesis pertain the influence of complimentary approach in holistic Arabic writing skills.This decision was based on the following experimental data μ1-μ2=16.36\ t4.704df(99)=000α2,\ ρ˂05 The acceptance of the alternative hypothesis on holistic Arabic writing skills was basedon the following experimental sub Arabic writing skills data.